Table ronde. Qu'est-ce qu'un rapport de forces dans les relations internationales ? / Jean-Baptiste DUROSELLE, Yves DURAND, Pierre MELANDRI, Jacques THOBIE, Roger BOURDERON - BOURDERON, Roger; DURAND, Yves; DUROSELLE, Jean-Baptiste; MELANDRI, Pierre; THOBIE, Jacques
//